1998
DOI: 10.1007/s11738-998-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channels and membrane disorders induced by drought stress in Vicia faba plants supplemented with calcium

Abstract: Wcia faba plants were grown under drought conditions and variously supplemented with calcium. Drought stress markedly inhibited the growth of Vicia faba plants. Ca 2+ ameliorated to a large extent this inhibition; fresh weight, dry mass, chlorophyll and water contents were variably improved. Membranes were, also, negatively affected by drought stress and percentage leakage was elevated, Concomitantly the efflux of + 2 + K and Ca was enhanced by drought but lowered by supplemental Ca 2+. In addition, membranes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“… Waraich et al (2012) reported that Ca is an essential nutrient for stomatal closure in chilling tolerant genotypes. Application of Ca in Vicia faba enhanced plant biomass, plant water relations, and chlorophyll content while reduced membrane leakage ( Abdel-Basset, 1998 ). Magnesium (Mg) also improve root morphological charcaters which helps to increase uptake of water and nutrients via roots, whlist boron nutrition enhances sugar transport in the plant body and improves seed germination and grain formation process ( Waraich et al, 2012 ).…”
Section: Management Strategiesmentioning
confidence: 99%
“… Waraich et al (2012) reported that Ca is an essential nutrient for stomatal closure in chilling tolerant genotypes. Application of Ca in Vicia faba enhanced plant biomass, plant water relations, and chlorophyll content while reduced membrane leakage ( Abdel-Basset, 1998 ). Magnesium (Mg) also improve root morphological charcaters which helps to increase uptake of water and nutrients via roots, whlist boron nutrition enhances sugar transport in the plant body and improves seed germination and grain formation process ( Waraich et al, 2012 ).…”
Section: Management Strategiesmentioning
confidence: 99%
“…In contrast to diuron, c was able to break down the membrane integrity since the ion leakage degree was parallel to the time increase at a low concentration of 200 mg/L. Likewise, the percentage of leakage by leaves of Vicia faba plants treated with calcium channel blockers of verapamil and nifedipine were greater than those of nontreated plants 15 . At a higher concentration of 300 mg/L, the properties of the light-dependent mechanism of action for c are more apparent.…”
Section: Discussionmentioning
confidence: 87%
“…This element also plays an essential role in regulating the properties of cytoplasmic membranes which are the first to respond to stresses: membrane disorders induced by drought in Vicia faba L. were ameliorated by supplemental Ca 2+ [11]. Due to such effects, calcium is widely applied in fruit production with the aim to improve fruit quality [9][10][11]. This aspect of its action was decisive for including calcium chloride in our investigations on the response of bedding plants to water stress.…”
Section: Digital Signaturementioning
confidence: 98%
“…A complex description of the Ca-controlled cascades of events occurring in plant cells under water stress can be found in a review by Hong-Bo et al [10]. This element also plays an essential role in regulating the properties of cytoplasmic membranes which are the first to respond to stresses: membrane disorders induced by drought in Vicia faba L. were ameliorated by supplemental Ca 2+ [11]. Due to such effects, calcium is widely applied in fruit production with the aim to improve fruit quality [9][10][11].…”
Section: Digital Signaturementioning
confidence: 99%
See 1 more Smart Citation